CLASSIFICATION OF STAKEHOLDERS ACTIVISM AIMING TO INFLUENCE CORPORATE SOCIAL RESPONSIBILITY - Danuta Dziawgo (Copernican Journal of Finance & Accounting, 2023)
The subject of this study is a pro-sustainable activism. The main focus is concentrated on both consumers and investors. The aim of the elaboration is to draw attention towards sustainable development trend in current economy. The purpose is to propose a classification of stakeholder activism that is being carried out to strengthen sustainable development of enterprises. The study proposed seven criteria for division of stakeholders activism that aim to increase Corporate Social Responsibility, which were then briefly characterized. Therefore, this article develops the theory with a new approach regarding stakeholders activism.